Mitigation of Efficiency Droop in an Asymmetric GaN-Based High-Power Laser Diode With Sandwiched GaN/InAlN/GaN Lower Quantum Barrier - Tian Lan; Guangzheng Zhou; Ying Li; Congcong Wang; Zhiyong Wang (IEEE Photonics Journal)
The phenomenon of efficiency droop is comprehensively investigated in an asymmetric GaN-based laser diode (LD). Numerical simulations and experiments are both conducted. It is found that with the introduction of a sandwiched GaN/InAlN/GaN lower quantum barrier (LQB) instead of the bulk GaN LQB in an asymmetric GaN-based high-power blue LD, the efficiency droop is effectively mitigated to only 9.7% under continuous-wave operation with no degradation in the crystal quality. Compared with the conventional asymmetric GaN-based LD, the wall-plug efficiency is successfully increased by 24.7% from 15.8% to 19.7% at high injection current of 2000 mA, promoting the increase of slope efficiency and output power, while the threshold current is reduced by 15.2%. These improvements are primarily attributed to the inserted high-quality InAlN thin barrier layer, which could form an extra potential barrier beneath the first InGaN quantum well to remarkably alleviate the hole overflow from the active region and enhance the radiative recombination rate.